Structural Study of the Hydration of Lipid Membranes Upon Interaction With Mesoporous Supports Prepared by Standard Methods and/or X‐Ray Irradiation - Marmiroli, Benedetta; Sartori, Barbara; Kyvik, Adriana R.; Ratera, Imma; Amenitsch, Heinz (Frontiers in Materials, 2021)
Mesoporous materials feature ordered tailored structures with uniform pore sizes and highly accessible surface areas, making them an ideal host for functional organic molecules or nanoparticles for analytical and sensing applications. Moreover, as their porosity could be employed to deliver fluids, they could be suitable materials for nanofluidic devices. As a first step in this direction, we present a study of the hydration of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) model lipid membranes on solid mesoporous support. POPC was selected as it changes structure upon hydration at room temperature. Mesoporous films were prepared using two different templating agents, Pluronic P123 (PEO-PPO-PEO triblock copolymer where PEO is Polyethylene Oxide and PPO is Polypropylene Oxide) and Brij 58 (C16H33(EO)20OH where EO is ethylene oxide), both following the conventional route and by X-ray irradiation via Deep X-ray lithography technique and subsequent development. The same samples were also additionally functionalized with a self-assembly monolayer (SAM) of (3-aminopropyl) triethoxysilane. For every film, contact angle was measured. A time resolved structural study was conducted using in situ Grazing Incidence Small Angle X-ray Scattering while increasing the external humidity RH, from 15 to 75% in a specially designed chamber. The measurements evidenced that the lipid membrane hydration on mesoporous films occurs at a lower humidity value with respect to the POPC deposited on silicon substrates, demonstrating the possibility to use porosity to convey water from below. A different level of hydration was reached by using the mesoporous thin film prepared with conventional methods or the irradiated ones, or by functionalizing the film using the SAM strategy, meaning that the hydration can be partially selectively tuned. Therefore, mesoporous films can be employed as “interactive” sample holders with specimens deposited on them. Moreover, thanks to the possibility to pattern the films using deep X-ray lithography, devices for biological studies of increasing complexity by selectively functionalizing the mesopores with biofunctional SAMs could be designed and fabricated.